What China will want: the future intensions of a rising power - Legro, Jeffrey W. (2007)
China's national power is growing rapidly, but what China will do with its newfound capabilities remains an issue of contentious debate among scholars and policymakers. At the heart of the problem is the difficulty of divining future intentions. Two arguments have dominated the debate. one focuses on power and likely Chinese revisionism. The other highlights China's growing inter-dependence and likely future satisfaction. Both are problematic in terms of logic and evidence. They offer linear projections that ignore the way that China's future is likely to be contingent - especially on the interaction of foreign policy ideas and events. Relative power and interdependence are important but their impact is mediated through the doctrines leaders use to justify action and establish authority: those ideas are prone to change in regular ways - and with them China's intentions. If this argument is right, policy prescriptions that advocate containing, engaging, or some mix of the two (i.e., hedging) in relations with China need to be reconfigured. - Reproduced.
Keywords: China - Foreign relations; International relations